KARAKTERISTIK PEDAGANG INFORMAL SEBAGAI â€œACTIVITY SUPPORTâ€ KORIDOR JALAN KINTAMANI - BATAM - Cia, Helen; Sarjono, Agung Budi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: The Maitreya school and tourists who came to Maha Vihara Duta Maitreya made the Kintamani corridor increasingly active, can be seen by the existence of shops as a formal activity which was followed by the proliferation of informal activities.Informal activities using road shoulder that should be provided as an emergency route are used as a place of activity where this activity also moves the economy and social activities for the road user community, this activity helps especially students, students and the surrounding community to fulfill their needs because of their superior location and more affordable prices, especially when compared to goods and services provided by formal traders.The phenomenon of Informal Activity as the Kintamani corridor support activity is the purpose of the research so that the structuring of the area of informal activities is better and safer for the perpetrators of the activity. The technique of survey primary data collection is through visual observations in the form of observations of